THE IMPLEMENTATION OF THE MERDEKA CURRICULUM TO FACILITATE ENGLISH GRAMMAR MASTERY OF THE JUNIOR HIGH SCHOOL STUDENTS - Alif S, Andi; Jabu, Baso; Muhalim, Muhalim (JTechLP: Journal of Technology in Language Pedagogy, 2024)
This study aims to determine how the implementation of the Merdeka Curriculum can facilitate the improvement of students' grammar mastery, especially the junior high school students and also, what are the challenges faced by teachers in implementing the Merdeka curriculum. This research uses descriptive qualitative methods. The participants in this study were grade 7 junior high school English teachers. Data collection was carried out by observation and interview. Based on the results of the interview in general, participants gave their responses about the concept of Merdeka curriculum and also how the implementation of Merdeka curriculum can facilitate the improvement of students' grammar mastery, especially in grade 7 junior high school students. The data results show that the teacher assesses that the concepts and learning methods in the Merdeka curriculum can facilitate improving students' grammar skills. Teachers also said that the challenges faced in implementing the Merdeka curriculum are the lack of technology-based teaching tools and some students' abilities that are considered not yet at the junior high school level.